PROFIL KESADARAN KEBERLANJUTAN (SUSTAINABILITY CONSCIOUSNESS) PADA SISWA SMA - Kelfina, Vidia; Fuadiyah, Sa’diatul; Fajrina, Suci; Rahmatika, Helsa (Universitas Cokroaminoto Palopo, 2025)
Sustainable Development Goals (SDGs) have definitions and principles that combine social, economic, and environmental aspects. Achieving SDGs requires a change in mindset and action called sustainability consciousness. In learning, teachers have linked SDGs with materials and projects related to sustainable development. However, students' concern for the environment is still low, so their level of sustainability consciousness is unknown. This study aims to analyze the profile of sustainability consciousness of high school students. This study is a descriptive type of research with quantitative methods. Data were collected through a questionnaire adapted from Gericke et al. (2019), consisting of 18 statements representing two indicators of sustainability consciousness, namely knowledge and attitude, covering three dimensions of SDGs including environment, social, and economy. Data analysis was carried out descriptively by grouping, tabulating, presenting, and calculating data. The results showed that the profile of sustainability consciousness of high school students was in the high category, with an average percentage of 76.38%. The knowledge aspect reached 76.38% and the attitude aspect 76.39%, both of which were in the high category. This shows that students have understood the concept of sustainability awareness and have begun to apply it in their daily lives.